An exploration of young people's, parent/carers', and professionals' experiences of a voluntary sector organisation operating a Youth Information, Advice, and Counselling (YIAC) model in a disadvantaged area - Shaima M. Hassan; Joanne Worsley; Lisa Nolan; Nicky Fearon; Adele Ring; Jane Shelton; David McEgan; Farheen Yameen; Esmaeil Morasae Khedmati; Cecil Kullu (BMC, 2022)
Abstract Background The present evaluation explored young people's, parents/carers, and healthcare professionals' perceptions of the Youth Information, Advice and Counselling (YIAC) model operated by a voluntary sector organisation in North West England. With an aim to understand the key components that contribute to enhancing the success of the YIAC model. Method Semi-structured interviews and focus groups with young people, parents/carers, and healthcare professionals were conducted. Data were analysed using thematic analysis. Results Five main themes were identified from the data: 1) Accessibility and flexibility; 2) Non-clinical model and environment; 3) Staff; 4) Partnership working; and 5) Promotion of positive mental health and wellbeing. Conclusion Findings highlight the importance of non-clinical, community-based, 'one-stop-shop' hubs for young people in disadvantaged areas. The key components highlighted as facilitating access and engagement include: opportunity to self-refer, choice of location, timely provision of support, non-clinical environment, age appropriate services, a non-hierarchical workforce, inclusive support for family and carers, a focus on wider, often social, issues, and collaboration with partner organisations. These findings suggest that early support hubs for young people's mental health should have consistent, long-term funding and should exist in every local area.